Psychologycal Literature Translation - Ika Oktaria Cahyaningrum (Surakarta English and Literature Journal, 2018)
Translation is a process of rewriting someone's ideas to dismiss without reducing understanding of the meaning and meaning to be conveyed. The scope of the translation is very broad, where translation is not only limited to translating a formal or informal text, but also at a level of aspects such as linguistics, literature and culture. The purpose of this paper is to link literary theory in the scope of translation where the aspects of literary psychology are the point of discussion at this writing